Effect of allopurinol in focal cerebral ischemia in rats: an experimental study - (:unkn) unknown (ELSEVIER SCIENCE INC, 2005)
Background: Allopurinol is a xanthine oxidase inhibitor that prevents the generation of free radicals and may play a role in the protection of the cells during cerebral ischemia. Methods: We evaluated the protective and therapeutic effect of allopurinol on reversible focal cerebral ischemia-reperfusion model in rats. Cerebral blood flow to the left hemisphere of adult Sprague-Dawley rats (n = 40) was temporarily interrupted by middle cerebral artery (MCA) and bilateral common carotid artery (CCA) occlusion for 3 hours in 5 groups of 8 rats each. Allopurinol (50 mg/kg) was given intraperitoneally 2 hours and immediately before ischemia and immediately and 2 hours after reperfusion in 4 different groups of rats, respectively. Animals were kept alive 24 hours after reperfusion. After sacrifice, infarction volumes and ratios of the brain slices were calculated, and the results were compared with those of the control group. Results: The difference between the allopurinol-administered group and the control group 2 hours before for both infarction volumes and infarction ratios achieved statistical significance. Regarding the allopurinol-administered group immediately before ischemia, infarction volumes and infarction ratios were diminished, but there was no statistically significant difference. The difference between allopurinol-administered and control group immediately after and 2 hours after reperfusion for both infarction volumes and infarction ratios achieved no statistical significance. Conclusion: This study showed that allopurinol has a protective effect, but not a therapeutic effect, on cerebral ischemia. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: allopurinol; focal cerebral ischemia; middle cerebral artery; reperfusion; XANTHINE-OXIDASE; URIC-ACID; FREE-RADICALS; ARTERY OCCLUSION; HYPOXIA-ISCHEMIA; BRAIN INJURY; STROKE; DAMAGE; PATHOPHYSIOLOGY; DEFEROXAMINE